PELATIHAN PENINGKATAN KESADARAN SISWA TERKAIT PERUNDUNGAN/BULLYING DI SEKOLAH DASAR INPRES PERUMNAS IV KOTA JAYAPURA - Patty, Sitti Rukmana; Lobo, Albertina Nasri (Universitas Sanata Dharma, 2024)
The phenomenon of bullying is currently rampant in educational institutions both at the elementary school and college levels. The rise of bullying cases at the elementary school level certainly requires special attention and cannot be underestimated. Therefore, solutions are needed to overcome bullying in schools. Activities to increase student awareness related to bullying at the elementary school level aim to reduce the number of bullying cases in educational institutions, especially at the elementary school level. The location of the service implementation was at SD Inpres Perumnas IV Jayapura City. The majority of students admitted that every day they practiced bullying their friends both in verbal and physical forms. They believed that this was a biased thing if it had not had a serious impact on the victim's condition. This service activity was done so that students know the forms of bullying and how they can overcome it early on as a form of their attitude to fight bullying activities that often occur in the educational environment. The results of increasing student awareness measured the success of the service activities, which was known by all components in the basic education institution including students, teachers, and education personnel.